Development of referee performance assessment instruments for athletic sports - Zikrur Rahmat; Heny Setyawati; Donny Wira Yudha Kusuma; Rumini (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The background of this study is that there is no standardized instrument to measure referees' abilities, so it is urgent to do research. In the future, with the existence of this instrument, it can be an evaluation material and benchmark for referee performance.